母乳喂养质量改进对极低和超低出生体重儿亲母母乳喂养率的影响 (Zhongguo Dang Dai Er Ke Za Zhi, 2016)
OBJECTIVE: To study the effect of breastfeeding quality improvement on the breastfeeding rate in very low birth weight (VLBW) and extremely low birth weight (ELBW) infants in the neonatal intensive care unit (NICU). METHODS: A retrospective analysis was performed for the clinical data of VLBW and ELBW infants who were admitted from July 2014 to July 2015 (pre-improvement group) and those who were admitted from August 2015 to June 2016 after the implementation of breastfeeding quality improvement measures (post-improvement group). The parameters including condition of breastfeeding (breastfeeding rate, breastfeeding amount, and breastfeeding time), duration of parenteral nutrition, time to enteral feeding, and incidence of feeding intolerance were compared between the two groups. RESULTS: The implementation of breastfeeding quality improvement measures significantly increased breastfeeding rate and amount, significantly shortened time to addition of human milk fortifier, duration of parenteral nutrition, and time to enteral feeding, and significantly decreased the incidence of feeding intolerance. CONCLUSIONS: Breastfeeding quality improvement measures can increase breastfeeding rate in the NICU and decrease gastrointestinal complications in preterm infants.